ATIVIDADE CAFEEIRA ENTRE PLANOS DE GOVERNO E INTEMPÉRIES CLIMÁTICAS: O caso da cafeicultura no Paraná (1960/1975) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
In Brazil, the impetus to expand and diversify industrial activities gave rise to the protection and stimulation of its main export products throughout the 20th century. Thus, over the years, different coffee price adjustments occurred in response to the international market. During the 1960s, the government of Paraná, the largest coffee producer in the country, showed a similar concern with strengthening industry, thus diversifying income generation mainly through the agricultural sector, and particularly for coffee. In addition to industrial development, the diversification of agriculture was encouraged to reduce dependence on coffee. This movement gained momentum during a time of coffee overproduction, at the beginning of the 1960s, in which eradication programs succeeded in reducing the supply of Brazilian coffee that met domestic and international demand. This provoked a need to renew plantation efforts, but rather than being based on expansionism, it focused on rational development, following the trend of agricultural modernization. However, in 1975 a strong frost occurred on July 18 that created a new situation for national coffee production. In Paraná, this phenomenon damaged a large percentage of the state’s coffee plantations, drastically reducing the next year’s harvest. After this frost, coffee production in Paraná did not return to the high levels of production reached in the previous decade, resulting in a reduction in land use based on coffee. Our research aims to demonstrate the retraction process of Paraná’s coffee cultivation, considering the political, economic, and ecological factors. We also demonstrate that, despite the relevance of the frost on July 18 for coffee production, which has become defining moment in the history of Northern Paraná, this event was only one of many determining factors in an ongoing process of modernization.
Keywords: Cafeicultura; Norte do Paraná; Modernização agrícola; Geada de 1975; Coffee cultivation; North of Paraná; Agricultural modernization; Frost of 1975; CNPQ::CIENCIAS HUMANAS::HISTORIA